Denormalising the Future Digital University: A feminist and Decolonial Perspective - Pischetola, Magda; Dirckinck-Holmfeld, Lone (Proceedings of the International Conference on Networked Learning, 2024)
Universities have become increasingly dependent from digital platforms and AI-assisted learning environments, with unprecedented investments in educational technologies during the pandemic. Generative AI is now raising new promises of a radical transformation of education, with machine learning supporting academic writing and customised learning. It is not surprising that the most normalised narrative about the future university is that it will be highly automated and datafied. Grounded in feminist and decolonial theories, this short essay poses questions to explore alternative imaginaries to this narrative. Feminist scholarship has contributed to epistemological relativism by questioning values that are embedded in techno-scientific knowledge production. It has pointed at the way rational modern subjectivity embraces homogeneity and denies difference, identifying equality with sameness. Adopting a feminist standpoint allows us to assess discursive-material attributes of technologies that are silencing differences. Critical/speculative questions following this approach could be: what does technology do in academic spaces? What are its political effects? How does/can it silence differences? Decolonial scholarship has shown how modernity is intricated with colonial logics, a relationship that is particularly evident in the rhetoric of progress and technological innovation. Most recently, it has stressed how digital technologies and AI shall be assessed in terms of their potential to oppress people and increase inequality. Decolonial thinkers focus on the subjectivities of those who are involved and consider institutions as a space for political action. Critical/speculative questions that go in this direction will ask: in the benefit of whom are technologies used in academic spaces? What are the invisible risks of these uses in terms of social justice? How do digital technologies reproduce social oppression? We argue that the dialogue between these theories can allow us to make the effort of denormalising the role of digital technologies in the future university and understanding how structural change might occur.